Analysis of relevant aspects of thermal and hydraulic modeling of electric machines. Application in an Open Self Ventilated machine. (22nd January 2015) - Malumbres, Jose A.; Satrustegui, Marco; Elosegui, Ibon; Ramos, Juan C.; Martínez-Iturralde, Miguel
Abstract: Prediction of the thermal behavior of electric motors in the early design stage is crucial in any design process. The most popular prediction methods are analytical, and based on the lumped parameter model approach. These methods require experimental data in order to obtain accurate results, but this data is often not available. This paper deals with the problem of the lack of experimental data for an Open Self-Ventilated (OSV) Induction motor and reviews some of the most controversial parameters in thermal modeling, such as the bearings model and the axial conductivity of the lamination stack. Due to the nature of the OSV machine, through ventilation is also investigated, and a hydraulic model with improvements focused on rotational effects observation is presented. Moreover, the heat transfer in end spaces and ducts is studied, using dimensionless analysis correlations, along with focusing on new hydraulic phenomena, such as the development of the flow and the roughness effect. An implementation of a thermal circuit for an OSV machine that has good agreement with reference results is used to compare heat transfer coefficients used regularly for Totally Enclosed Fan Cooled (TEFC) enclosures. Finally, a sensitivity analysis is carried out on some parameters to determine their importance. Highlights: Coupled hydraulic and thermal models for an OSV induction machine are presented. Different approaches to calculate some parameters for electric machines are proposed. The use of dimensionless correlations for the calculation of convection is suggested. The results from the models are compared against reference values, and then analyzed. The relative importance of some parameters through a sensitivity analysis is reasoned.